Evolusi Kurikulum Pendidikan Agama Islam di Sekolah Menengah Umum: Tinjauan Historiografis Berbasis Literatur Kebijakan - Ansorul Alim; Dwi Ratnasari (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2026)
The Islamic Religious Education (PAI) curriculum in senior high schools serves as a space of ideological contestation between the sociopolitical interests of the ruling authorities and the spiritual rights of citizens. This study aims to conduct a historiographical review of the evolution of the senior high school PAI curriculum through a critical analysis of official policy documents across political regimes from 1975 to 2025. Employing a qualitative approach with a historical-policy design, this library research applies historical methods to national regulatory documents and related literature. The thematic analysis reveals that the senior high school PAI curriculum has transformed through three major paradigms. During the New Order era (1975–1994), PAI functioned in a centralized manner as an apparatus of moral engineering to maintain regime stability. The Reform era (2000–2006) marked a decentralization process that restored pedagogical sovereignty to teachers, although it also triggered fragmentation in regional content control. In the contemporary era (2013–2025), through the Merdeka Curriculum and Minister of Primary and Secondary Education Regulation Number 13 of 2025, PAI has been reconstructed as an instrument of conflict resolution through the internalization of Religious Moderation. This study concludes that the senior high school PAI curriculum reflects a utilitarian form of state anxiety. The success of this transformation ultimately depends on the critical capacity of local educators.